BO‘LAJAK JISMONIY MADANIYAT VA SPORT O‘QITUVCHILARINING MA’NAVIY-AXLOQIY TARBIYASINI SHAKLLANTIRISH - Abdukarimov, N.A.; Tuychiyev, S.S. (SCIENCE and SOCIETY, 2020)
This article considers the role of physical education in circle classes to the spiritual upbringing of the students in Higher Educational institutions.
Keywords: audience; spirituality; ethics; sports; gymnastics; sports clubs; moral culture